O seguro-desemprego do pescador artesanal: Os recursos pesqueiros, os defesos e sua incidência territorial, a operacionalizaç\~ao dos pagamentos e estimativas do "vazamento" de recursos públicos (2013-2024) - Jo\~ao Paulo Viana (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– Unemployment insurance for professional artisanal fishermen is probably one of the federal programs with the longest history of evaluations and audits by control bodies, due to recurring complaints and findings of fraud. This study presents the territorial incidence of closed fishing seasons operated in 2017, the last year that such information was made available, and information about the operation of the program, such as the flow of beneficiaries and an estimate of the amount of installments unduly paid to beneficiaries between January 2013 and June 2024, obtained from the application of a methodology developed by this research into the administrative records of the program's operation. The results indicate that there was a deterioration in the quality of the program's operation after the processing of applications left the Ministry of Labor and Employment (MTE) and went to the National Social Security Institute (INSS) in 2015. Among the main shortcomings, it is notable that a program of this scale and with such a significant budgetary impact does not have a centralized monitoring system, along the lines - at least - of the one that existed when operated by the MTE. The estimated "leakage" of public resources in almost 12 years was estimated to be between R 2 and R 9 billion, with it being more likely to be close to the upper limit. It is recommended that an audit be carried out covering the most recent period, starting in 2019, to accurately detail the results outlined by the research and to advance in proposing measures to correct and improve the program.
Keywords: I38; J08; J65; Q000; Q22; Q28; 330; unemployment insurance; fisheries closed season insurance; fisheries resources